Can guarantees effectively leverage financing for SMEs in low- and middle-income countries? - Bao-We-Wal Bambe (German Institute of Development and Sustainability (IDOS), 2025)
Achieving the Sustainable Development Goals (SDGs) will require significant financing and investment, particularly as growing challenges from climate events highlight the insufficiency of public funds to meet the 2030 Agenda (World Economic Forum 2024). Private capital for low- and middle-income countries (LMICs) surged in recent years, with significant commitments from multilateral development banks (MDBs). However, the financing gap to achieve the SDGs remains sizable, highlighting the need for greater effort to mobilise much larger private capital for sustainable development. In recent years, guarantees have emerged as a key leveraging mechanism. They are designed to mitigate high investment risks to support private capital mobilisation in LMICs. However, despite some progress, guarantees are used sparingly, suggesting considerable scope for increasing their scale, as highlighted by the G20 Independent Expert Group (IEG). This Policy Brief examines whether guarantees can serve as an effective leveraging mechanism for small and medium-sized enterprises (SMEs) in low- and middle-income countries (LMICs). This is especially so because SMEs remain largely hampered by poor access to finance, despite their key role in providing jobs for the local population and contributing to economic growth. Moreover, in the face of climate change, SME adaptation requires new investments in climate-resistant technologies and clean energies, highlighting the need for additional financing amid severe constraints on access to capital. Guarantees can complement other leveraging mechanisms, further easing financing constraints for SMEs in LMICs. Guarantees can absorb some of the risks associated with investment, offering financial institutions greater security. This added security can, in turn, help improve access to capital for SMEs. On the other hand, they can also help catalyse private sector investment in LMICs. Recognising both the potential benefits and short-comings of guarantees, this Policy Brief provides the following policy recommendations on how guarantees could be extended efficiently to the SME sector in LMICs. - Guarantees should be directed at financial institu-tions to mitigate portfolio risk and actively promote lending to small projects or SMEs in high-risk sectors, particularly those with the potential to generate substantial economic, environmental, or social benefits. - Complement guarantees with additional measures to improve SMEs' financial management, enhance risk assessment, and strengthen technical capacity through professional training and advisory services. - Implement partial credit guarantees to require financial institutions to retain a share of the risk, thereby reducing moral hazard and promoting rigorous analyses of borrowers' creditworthiness. Complement these guarantees with conditionalities and monitoring criteria, such as regular reporting, to ensure the incrementality and additionality of guaranteed financing. Enhance the harmonisation of guarantees with other leveraging mechanisms, improve coordination among MDBs and DFIs, and streamline guarantee frameworks to achieve greater efficiency. - Recognise that guarantees alone cannot address structural vulnerabilities and institutional weakness in LMICs; a long-term commitment from decision-makers is essential to improve institutional and economic performance.
Keywords: 320; Guarantees; Multilateral Developemnt Banks; Small and Medium-Sized Enterprises; Low- and Middle-income Countries; 2030 Agenda